A Transparent Polymer-Composite Film for Window Energy Conservation - Liu, Xianhu; Zhang, Haoyu; Pan, Yamin; Ma, Jun; Liu, Chuntai; Shen, Changyu (Nano-Micro Letters, 2025)
As living standards improve, the energy consumption for regulating indoor temperature keeps increasing. Windows, in particular, enhance indoor brightness but also lead to increased energy loss, especially in sunny weather. Developing a product that can maintain indoor brightness while reducing energy consumption is a challenge. We developed a facile, spectrally selective transparent ultrahigh-molecular-weight polyethylene composite film to address this trade-off. It is based on a blend of antimony-doped tin oxide and then spin-coated hydrophobic fumed silica, achieving a high visible light transmittance (> 70%) and high shielding rates for ultraviolet (> 90%) and near-infrared (> 70%). When applied to the acrylic window of containers and placed outside, this film can cause a 10 °C temperature drop compared to a pure polymer film. Moreover, in building energy simulations, the annual energy savings could be between 14.1% 31.9% per year. The development of energy-efficient and eco-friendly transparent films is crucial for reducing energy consumption and promoting sustainability in the window environment. Highlights: 1 The resultant film offers high visible light transmittance (>70%) while effectively blocking UV (>90%) and NIR (>70%) radiation, addressing the balance between natural lighting and solar energy control. 2 Incorporating hydrophobic silica, it achieves high emissivity for radiative cooling, reducing indoor temperatures by up to 10 °C and achieving maximum additional cooling energy savings of 261 MJ m−2 per year. 3 Its superhydrophobic surface ensures excellent self-cleaning properties and durability, making it highly suitable for long-term outdoor applications.